PENYELESAIAN PERKARA TINDAK PIDANA PENCURIAN MELALUI MEKANISME RESTORATIVE JUSTICEN (STUDI KASUS LAPORAN POLISI NOMOR:LP/B/22/IX/2022/SPKT/POLSEK LENDAH) - Irwan Hardiyanto; Sigit Herman Binaji (Fakultas Hukum Universitas Janabadra, 2023)
The research aimed to analyze the idea emerged of a punishment system that is oriented towards the recovery of the victim and the victim’s suffering, which is called restorative justice. Because the victim is the party that has suffered the most from the crime. As for the research it use nornative juridical research type based on fact about the the settlement of the crime of theft through restorative justice mechanism which is described in a descriptive analysis. The approach method in this research is the statutory approach and conceptual approach. The research method used in this study is is normative juridical originating from primary data obtained from interviews and secondary data from literature studies. The resulst of the study show that the settlement of the crime of theft through restorative justice mechanism is carried out quite successfuly and efficiently, especially for the recovery of victime, and provides benefits including increasing acces to justice in society, accelerating the case settlement process, reducing litigation cost so that a speedy criminal process is realizedt, simple and low cost, realizing justice and benefit without compromising legal certainty, restoring the condition of the victim, avoiding the negative stigma of the perpetrator in society and restoring friendly relations between victims and perpeprators and their families